Activated carbon-graphene nanoplatelets based green cooling system: Adsorption kinetics, heat of adsorption, and thermodynamic performance. (15th February 2020) - Rupa, Mahua Jahan; Pal, Animesh; Saha, Bidyut Baran
Abstract: This study presents the adsorption kinetics and thermodynamic analysis of green cooling systems employing activated carbon-graphene composite/ethanol pairs. Instantaneous adsorption uptake of these pairs is experimentally measured at various adsorption and evaporation temperatures. The measured data are fitted with the widely used two kinetics models; viz., Fickian diffusion (FD) and linear driving force (LDF) models and between them LDF shows better to track the behavior of the instantaneous uptake of the studied pairs. The diffusion time constant and activation energy are determined for all pairs. Uptake and temperature dependency heat of adsorption is also analyzed. The thermodynamic performance parameters have been computed employing time-independent cooling cycle at three evaporation temperatures of 5, 10, and 15 °C with a function of different heat source temperatures. Theoretical analysis demonstrates that the composite/ethanol pairs possess high cooling effect which will provide notable direction to develop next-generation cooling systems. Graphical abstract: Image 1 Highlights: Enhanced thermal conductive composites are employed for cooling applications. Adsorption kinetics has been investigated experimentally and theoretically. Diffusion time constant and activation energy are determined. Uptake and temperature dependency isosteric heats of adsorption are calculated. Thermodynamic performances are investigated at different operating conditions.